2015
DOI: 10.1167/iovs.14-15496
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Stimulates Proliferation and Expression of Mucin and Immunomodulatory Genes in Cultured Conjunctival Goblet Cells

Abstract: This study demonstrated that conjunctival goblet cells are IL-13 responsive cells that produce factors known to maintain epithelial barrier, stimulate mucin production, and modulate immune response in nonocular mucosa when treated with IL-13. The functional significance of IL-13-stimulated factors remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 58 publications
(71 reference statements)
8
82
0
Order By: Relevance
“…Analyses of the GO categories included several genes, which are relevant to cell proliferation, cell migration and invasion. As evidence has suggested that S100A6 regulates the levels of certain genes involved in cell proliferation, including IL-8 (24), IL-2 (25), IL-13 (26), IL-6R (27), CDK4 (28), CDK5 (29), MCM7 (30), Bcl2 (29) and MYC (31), these genes were selectively assessed. To confirm and to evaluate their expression levels, mRNA quantification was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of the GO categories included several genes, which are relevant to cell proliferation, cell migration and invasion. As evidence has suggested that S100A6 regulates the levels of certain genes involved in cell proliferation, including IL-8 (24), IL-2 (25), IL-13 (26), IL-6R (27), CDK4 (28), CDK5 (29), MCM7 (30), Bcl2 (29) and MYC (31), these genes were selectively assessed. To confirm and to evaluate their expression levels, mRNA quantification was performed.…”
Section: Discussionmentioning
confidence: 99%
“…They also produce factors that maintain homeostasis and immune tolerance on the ocular surface. 109, 179 The worst cornea disease develops in dry eye conditions with loss of goblet cells, such as Sjögren syndrome, Stevens-Johnson syndrome and graft-vs.-host disease. 134, 180, 181 The Th1 cytokine IFN-γ inhibits goblet cell secretion and promotes apoptosis of these cells.…”
Section: Future Directions For Researchmentioning
confidence: 99%
“…Immunohistochemical assay of the keratin has been subsequently used to identify goblet cells in cultures of conjunctival epithelial cells (Shatos et al, 2001; Tukler Henriksson et al, 2015). In recent comparative microarray studies of conjunctival RNA from wild type mice and Spdef null mice lacking goblet cells, no change in keratin 7-gene expression could be found with the loss of the goblet cells suggesting that the keratin may not be goblet cell specific (Marko et al, 2013).…”
Section: Goblet Cell Products and Specific Cell Markersmentioning
confidence: 99%
“…Histology of these cells show stratified layers of cells that do not appear to be polarized nor does one see in published figures a mucin granule filled cytoplasm. Thus the cells of the culture system lack classic goblet cell morphology (Contreras-Ruiz and Masli, 2015; Shatos et al, 2001; Tukler Henriksson et al, 2015). …”
Section: Models For Study Of Goblet Cell Function/biologymentioning
confidence: 99%